Analysis of Employee Engagement, Relational Capital, and Competitive Advantage on Employee Performance Leo Shoe Industry House in Mojokerto - Arif, Amisha Novita; Sukarno, Gendut; Dewanti, Mentari Clara (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to assess the influence of employee engagement, relational capital, and competitive advantage on employee performance at the Leo Shoe Industry House in Mojokerto. The population in this study were 40 employees of the Leo Shoe Industry House in Mojokerto. The sampling technique in this study uses saturated sampling technique or census sampling, where all members of the population are sampled. The data set consists of two types: primary data, which is obtaioned from respondents answers to the questionnaire. And secondary data, which is sourced from internal data of the Leo Shoe Industry House in Mojokerto. Data analysis was conducted using the Partial Least Squares (PLS) technique. The results showed 1) Employee engagement (X1) has a positive and significant effect on employee performance (Y) with a path coeffisient value of 0,288 and a p-values of 0,007. 2) Relational capital (X2) has a positive and significant effect on employee performance (Y) with a path coefficient value of 0,447 and a p-values of 0,000. 3) Competitive advantage (X3) has a positive and significant effect on employee performance (Y) with a path coefficient value of 0,291 and a p-values of 0,006.